PENGGUNAAN MEDIA EDUKATIF KARTU DOMINO UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII.9 MTS NEGERI DUMAI TAHUN PELAJARAN 2017/2018 - sumini sumini (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research is a Classroom Action Research that have aimed to improve students learning result on the subject of Linear Equation with One Variable using media educative Domino Card games in the class VII.9 MTs Negeri Dumai on odd semester, academic year 2017/2018. This class consisting of 37 students with 17 male students and 20 female students. This research was conducted in two cycles comprising 3 meetings in each cycle. The data of the research were collected by using some techniques, that is by using test after each cycle and observation each meetings. The data of was collecting using quantitative and qualitative analyze. The result of this research using media educative Domino Card games can improve students learning result. There was an improvement on the mean score of the test. In the first cycle it was 74.05 and improved to 84.32 in the second cycle. This technique could make the students pay attention to the lesson properly.